Erratum: FORSMAN, Z. H. & BIRKELAND, C. (2009) Porites randalli: a new coral species (Scleractinia, Poritidae) from American Samoa. Zootaxa, 2244, 51–59. - Forsman, Z. H.; Birkeland, C. (Zootaxa, 2009)
(Erratum)